INCREASING THE BEARING CAPACITY OF SQUARE FOUNDATIONS BASED ON SOYBEAN BIO-CEMENTATION - Annas Dwi Safi'i; Agata Iwan Candra; Mahardika Kamalika Khusna Ali (LPPM Universitas Negeri Jakarta, 2025)
Sandy soils are commonly employed as the foundation for shallow footings. However, their relatively low bearing capacity often leads to excessive settlement and deformation. This study examines the potential application of the Enzyme-Induced Carbonate Precipitation (EICP) technique based on soybeans. Utilizing urease derived from soybeans to catalyze the crystallization of calcium carbonate (CaCO₃). This research investigates the impact of EICP-induced carbonate precipitation on the bearing capacity of sandy soil in square footings. 4 x 4 cm footing model was tested using the AIC-Innovation Loading Test apparatus. Direct shear additional tests were performed to assess differences in increase cohesion and shear angle. The results show 174.90% increase in bearing capacity, 73.47% reduction in settlement, 300.64% increase in cohesion from the shear test, and 202.46% increase from the loading test. The shear angle increased by 56.34%, and the dry unit weight increased by 36.5%. ANOVA analysis with a p-value of 2.03 × 10⁻¹⁵ < 0.05 confirmed that the increase in bearing capacity was not due to random variation but to the EICP treatment. These findings demonstrate that EICP proves to be a viable technique to enhance sandy soil and contributes to advancing of bio-cementation based on organic materials as a sustainable solution.